KEHILANGAN HASIL PASCA PANEN KEDELAI PADA PROSES PERONTOKAN MENGGUNAKAN MESIN PERONTOK KEDELAI TIPE MPT001 - Jovanka P. Lengkey; Lady C. Ch. E. Lengkey; Frans Wenur (COCOS, 2021)
Abstract The purpose of this study was to describe the operating conditions and performance of the soybean thresher MPT001 type during the threshing process, determine the total losses in threshing process using soybean thresher machine MPT001 and determine the rendemen of soybean thresher machine type MPT001. The results showed that the average engine rotation per minute 639.24 RPM and the average thresher capacity was 33.19 kg/h (grain) at 17,8 % moisture content. The results also show that losses of soybean threshing are those unthreshed soybean seed at the output hole averaged (5.23 ± 0.26) % and the losses are those unthreshed soybean seed that escape the thresher at the rear with stove (2.51 ± 0.81) %. Total loss of threshing used MPT001 type soybean thresher machine is (7.74 ± 0.92) %. The yields of machine 18.18 %, 18.06 % and 18.93 % respectively with an average of 18.39 %. Key words: soybean, thresher, machine performance, losses, yields